Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
i think that supposed to be (wx - y^2)^2?
If so, multiply using FOIL:
First: wx * wx = w^2x^2
Outside: wx * -y^2 = -wxy^2
Inside: -y * wx = -wxy^2
Last: -y^2 * -y^2 = y^4
Combine w^2x^2 - 2wxy^2 + y^4
If so, multiply using FOIL:
First: wx * wx = w^2x^2
Outside: wx * -y^2 = -wxy^2
Inside: -y * wx = -wxy^2
Last: -y^2 * -y^2 = y^4
Combine w^2x^2 - 2wxy^2 + y^4
Answer:
I believe it is wx^2 - 2ywx + y^2
Step-by-step explanation:
seperated into (wx-y)(wx-y) and used FOIL
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.